Water-based sizing agent for fibers as well as preparation method and application of water-based sizing agent
By using an aqueous sizing agent composed of polyamic acid salt and sulfonated polyaramide or lignin sulfonate, the problem of poor interface bonding between the fiber and the polyamide matrix is solved, and an efficient interface strengthening and environmentally friendly processing process is achieved.
Patent Information
- Application Number
- CN202411973591.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
The compatibility of existing fiber sizing agents with polyamide matrix is poor, resulting in poor interfacial bonding between the fiber and the polyamide matrix.
An aqueous sizing agent for fibers, including polyamide salts and sulfonated polyaramide or lignin sulphonates, is provided to improve the interface bond strength between the fiber and the polyamide matrix through surface modification technology of the sizing agent.
The interface bonding strength between the fiber and the polyamide matrix is significantly improved, the mechanical properties of the composite material are improved, and the aqueous sizing agent is environmentally friendly, has high safety and good processability.
Smart Images

Figure CN119777160A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sizing agents, and in particular to an aqueous sizing agent for fibers and a preparation method and application thereof. Background Art
[0002] Fiber-reinforced thermoplastic resin-based composites have received extensive attention in the fields of aerospace, automobiles, civil engineering, and medicine. Among thermoplastic resin matrices, polyamide has excellent mechanical properties and is widely used in general fields such as automobiles. Effective fiber surface treatment to improve the interfacial wetting effect between the fiber and the polyamide matrix is crucial to the mechanical properties of the composite.
[0003] Fiber treatment with sizing agents is a common method for surface modification of reinforcements, which is easy to operate, efficient, and easy to engineer. However, currently, the most common fiber sizing agents are mainly epoxy sizing agents, which have poor compatibility with polyamide matrix, resulting in poor interfacial bonding between the fiber and the polyamide matrix.
[0004] Therefore, developing a fiber sizing agent that can increase the interfacial bonding strength between the fiber and the polyamide matrix is a technical problem that needs to be solved urgently in this field. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide an aqueous sizing agent for fibers and a preparation method and application thereof. The aqueous sizing agent for fibers provided by the present invention can increase the interfacial bonding strength between the fibers and the polyamide matrix.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides an aqueous sizing agent for fibers, the aqueous sizing agent for fibers comprising component 1, component 2 and water, wherein component 1 is polyamic acid salt, and component 2 is at least one of sulfonated polyaromatic amide and lignin sulfonate; based on 100 parts by weight of the total parts by weight of the aqueous sizing agent for fibers, the aqueous sizing agent for fibers comprises the following components in parts by weight:
[0008] Component 1: 0.1-15 parts;
[0009] Component 2: 0.1-15 parts;
[0010] Water: 70-99.8 parts.
[0011] The aqueous sizing agent for fibers provided by the present invention can increase the interfacial bonding strength between the fibers and the polyamide matrix.
[0012] Further, the water includes deionized water;
[0013] And / or, the main chain of the molecule of component 1 contains a fatty chain structure, and the main chain of the molecule of component 2 contains a heterocyclic structure;
[0014] And / or, the component 1 is a polyamic acid ammonium salt formed by polyamic acid and an amine compound.
[0015] Further, the polyamic acid is prepared by polymerization of a dianhydride monomer and a diamine monomer, wherein the dianhydride monomer includes at least one of 1,2,3,4-butanetetracarboxylic dianhydride, cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, 1,2,3,4-cyclohexanetetracarboxylic dianhydride, pyromellitic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 4,4'-biphenyl ether dianhydride, and 3,4,3',4'-biphenyltetracarboxylic dianhydride. The diamine monomer includes at least one of hexamethylenediamine, 1,5-diamino-2-methylpentane, nonanediamine, 3-methylheptanediamine, 4,4-dimethylheptanediamine, decanediamine, polyethylene oxide diamine, 2,2′-(ethylenedioxy)diethylamine, bis(3-aminopropyl)amine, 1,4-bis(3-aminopropyl)piperazine, diaminobutene dinitrile, polyether diamine, 1,4-cyclohexanediamine, 5-amino-1,3,3-trimethylcyclohexanemethylamine, 4,4′-diaminodicyclohexylmethane, and 3,3′-dimethyl-4,4′-diaminodicyclohexylmethane;
[0016] And / or, the structural formula of the polyamic acid is as follows:
[0017]
[0018] Wherein, n is a natural number greater than 0;
[0019] Ar1 is at least one of the following structures:
[0020]
[0021] -L- is at least one of the following structures:
[0022]
[0023] Furthermore, the polyamic acid has at least one of the following structural formulas:
[0024]
[0025] And / or, the number average molecular weight of the polyamic acid is in the range of 1000 to 100000 g / mol;
[0026] And / or, the amine compound includes at least one of ammonia water, diethanolamine, triethanolamine, triethylamine, and N,N′-dimethylethanolamine.
[0027] Further, the structural formula of the sulfonated polyaromatic amide is as follows:
[0028]
[0029] Wherein, n is a natural number greater than 0;
[0030] R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 are the same or different and each independently represents hydrogen, sulfonic acid group or salt-type sulfonic acid group;
[0031] Ar2 is one or more of the following structures:
[0032]
[0033] Among them, R 14 , R 15 , R 16 , R 17 , R 18 , R 19 , R 20 , R 21 , R 22 , R 23 , R 24 , R 25 , R 26 , R 27 , R 28 , R 29 , R 30 , R 31 , R 32 , R 33 , R 34 , R 35 , R 36 , R 37 , R 38 , R 39 , R 40 , R 41 , R 42 , R 43 , R 44 , R 45 , R 46 , R 47 , R 48 , R 49 are the same or different and each independently represents hydrogen, sulfonic acid group or salt-type sulfonic acid group;
[0034] And / or, the sulfonated polyaromatic amide has at least one of the following structural formulas:
[0035]
[0036]
[0037] and / or, the lignin sulfonate comprises sodium lignin sulfonate;
[0038] and / or, the number average molecular weight of the sulfonated polyaromatic amide is 1000 to 100000 g / mol;
[0039] and / or, the number average molecular weight of the lignin sulfonate is 1000-250000 g / mol;
[0040] And / or, the fiber includes at least one of carbon fiber, basalt fiber, quartz fiber, glass fiber, and silicon carbide fiber.
[0041] In a second aspect, the present invention provides a method for preparing the aqueous sizing agent for fibers as described in the first aspect, the preparation method comprising the following steps:
[0042] Dissolving the component 1 in the water to obtain a component 1 solution;
[0043] Dissolving the component 2 in the water to obtain a component 2 solution;
[0044] The component 1 solution and the component 2 solution are mixed to obtain the aqueous sizing agent for the fiber.
[0045] Furthermore, in the component 1 solution, the mass ratio of the component 1 to the water is 1:(4-100);
[0046] and / or, the particle size of the component 1 solution ranges from 5 to 4500 nm;
[0047] and / or, in the component 2 solution, the mass ratio of the component 2 to the water is 1:(0.5-500);
[0048] And / or, the particle size range of the component 2 solution is 5 to 4500 nm.
[0049] In a third aspect, the present invention provides a use of the aqueous sizing agent for fibers as described in the first aspect in fibers.
[0050] Specifically, a modified fiber, the preparation process of the modified fiber comprises the following steps: immersing unsized or desized fiber bundles in the aqueous fiber sizing agent as described in the first aspect, and drying after sizing to obtain the modified fiber.
[0051] A fiber-reinforced polyamide resin composite material comprises the modified fiber and polyamide resin.
[0052] Compared with the prior art, the beneficial effects of the present invention include at least one of the following:
[0053] (1) The aqueous sizing agent for fibers provided by the present invention can increase the interfacial bonding strength between the fibers and the polyamide matrix.
[0054] (2) The aqueous sizing agent for fibers provided by the present invention uses water as solvent, is environmentally friendly, highly safe and heat-resistant, and can meet the processing temperature of polyamide. After sizing the fibers, the dried fibers have flexibility, which reduces the risk of fuzzing and fiber breakage during subsequent processing of the fibers and has good processability.
[0055] (3) The preparation method of the aqueous fiber sizing agent provided by the present invention is simple, efficient, easy to repeat, and has broad industrial application prospects.
[0056] (4) The aqueous sizing agent provided by the present invention has stable physical and chemical properties and excellent hydrophilicity. Since the aqueous sizing agent provided by the present invention contains a heterocyclic structure in its components, the overall thermal deformation temperature is significantly improved, and the composite material prepared based on the mortise and tenon interlocking structure has stable interface bonding force at high temperature.
[0057] (5) The water-based sizing agent provided by the present invention has wear-resistant properties. Since its components all contain aromatic rings and aromatic (nitrogen) heterocyclic groups, it has good friction resistance, reduces the amount of hairiness in the fiber yarn-laying process, and improves the adaptability of the composite material manufacturing process. It is particularly suitable for the composite manufacturing of fibers and high-viscosity thermoplastic resins.
[0058] (6) The aqueous sizing agent of the present invention contains a flexible fatty chain structure, and the sized fiber has flexibility after drying, which reduces the risk of fiber breakage during fiber processing; the sizing agent fills the original defects and grooves on the fiber surface, thereby improving the tensile strength of the fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0060] Figure 1 The following are scanning electron microscope photos of the desized carbon fiber fabric and the sized carbon fiber fabric obtained in Example 1 of the present invention;
[0061] Figure 2 This is a scanning electron microscope photograph of a cross section of a sample after a bending test of the desized carbon fiber fabric / polyamide 6 resin composite material in Comparative Example 1 of the present invention;
[0062] Figure 3 This is a scanning electron microscope photograph of a cross section of a specimen after a bending test of the sized carbon fiber fabric / polyamide 6 resin composite material in Example 1 of the present invention;
[0063] Figure 4 These are digital photos of the sized carbon fiber tow and the desized carbon fiber tow in Example 1 of the present invention. DETAILED DESCRIPTION
[0064] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0065] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0066] This invention was funded by the National Key R&D Program, project number: 2024YFB3712801.
[0067] In a first aspect, the present invention provides an aqueous sizing agent for fibers, the aqueous sizing agent for fibers comprising component 1, component 2 and water, wherein component 1 is polyamic acid salt, and component 2 is at least one of sulfonated polyaromatic amide and lignin sulfonate; based on 100 parts by weight of the total parts by weight of the aqueous sizing agent for fibers, the aqueous sizing agent for fibers comprises the following components in parts by weight:
[0068] Component 1: 0.1-15 parts (for example, 0.1 parts, 1 parts, 3 parts, 5 parts, 7 parts, 9 parts, 11 parts, 13 parts or 15 parts);
[0069] Component 2: 0.1-15 parts (for example, 0.1 parts, 1 parts, 3 parts, 5 parts, 7 parts, 9 parts, 11 parts, 13 parts or 15 parts);
[0070] Water: 70 to 99.8 parts (for example, 70 parts, 80 parts, 90 parts or 99.8 parts).
[0071] The aqueous sizing agent for fibers provided by the present invention uses water as a solvent, is environmentally friendly, has high safety, has stable physical and chemical properties, excellent hydrophilicity, and strong heat resistance, can meet the processing temperature of polyamide, and after the fibers are treated, the dried fibers have flexibility, and the risks of fuzzing and fiber breakage in subsequent processing of the fibers are reduced, and the processability is good, and the interface bonding strength between the fibers and the polyamide matrix can be high.
[0072] The present invention is directed to fiber-reinforced polyamide composite materials, and proposes a method suitable for improving the interfacial properties of fibers and resin matrices. Specifically, polyamic acid salt, sulfonated polyaromatic amide or lignin sulfonate are compounded into an aqueous sizing agent, and the fiber is surface-coated and modified by a sizing method. The polyamic acid salt, sulfonated polyaromatic amide or lignin sulfonate described in the present invention can be emulsified into hydrophilic nanoparticles in water, and the fibers are attached to the fiber surface after sizing and drying. Among them, the main chain of component 1 polyamic acid salt contains flexible aliphatic carbon, has stretching and curling characteristics, and the main chain has sufficient free volume movement, and the rigid structure of aromatic rings or heterocyclic rings is contained in the molecular chain of component 2 sulfonated polyaromatic amide or lignin sulfonate, and the free volume movement ability is weak, and the sizing agent components all have strong molecular effects (van der Waals force, hydrogen bond, π-π stacking) on the matrix. After heat treatment, with the volatilization of the solvent and the imidization of the polyamic acid, the two-component sizing agent molecular microparticles on the surface approach each other to reach a dense filling state, and the molecular chains between the particles diffuse with each other to form a homogeneous sizing agent membrane structure with a certain mechanical strength. During the composite material molding process, due to the different free volume changes of the two-component resins on the fiber surface under heating, the matrix resin and the fiber surface form a non-uniform infiltration. This infiltration method increases the total fracture area of the crack in the matrix, thereby increasing the dissipation of energy, thereby achieving the effect of strengthening the interface. At the same time, the fibers after sizing have good bundling, low hair content, high wear resistance, and good protection for the fiber surface.
[0073] In the above aqueous sizing agent for fibers, as an optional implementation, the water includes deionized water.
[0074] In the above aqueous sizing agent for fibers, as an optional implementation, the main chain of the molecule of component 1 contains a fatty chain structure, and the main chain of the molecule of component 2 contains a heterocyclic structure.
[0075] In the above aqueous sizing agent for fibers, as an optional implementation, the component 1 (polyamic acid salt) is a polyamic acid ammonium salt formed by polyamic acid and an amine compound.
[0076] In the above-mentioned aqueous sizing agent for fibers, as an optional embodiment, the polyamic acid is used as a precursor of polyimide, which is prepared by polymerization of dianhydride monomers and diamine monomers, wherein the dianhydride monomers include 1,2,3,4-butanetetracarboxylic dianhydride, cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, 1,2,3,4-cyclohexanetetracarboxylic dianhydride, pyromellitic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 4,4'-biphenyl ether dianhydride, 3,4,3',4' At least one of biphenyltetracarboxylic dianhydride, the diamine monomer includes hexamethylenediamine, 1,5-diamino-2-methylpentane, nonanediamine, 3-methylheptanediamine, 4,4-dimethylheptanediamine, decanediamine, polyethylene oxide diamine, 2,2′-(ethylenedioxy)diethylamine, bis(3-aminopropyl)amine, 1,4-bis(3-aminopropyl)piperazine, diaminobutene dinitrile, polyether diamine, 1,4-cyclohexanediamine, 5-amino-1,3,3-trimethylcyclohexanemethylamine, 4,4′-diaminodicyclohexylmethane, and 3,3′-dimethyl-4,4′-diaminodicyclohexylmethane.
[0077] In the above-mentioned aqueous sizing agent for fibers, as an optional embodiment, the structural formula of the polyamic acid is as follows:
[0078]
[0079] Wherein, n is a natural number greater than 0;
[0080] Ar1 is at least one of the following structures:
[0081]
[0082] -L- is at least one of the following structures:
[0083]
[0084] In the above aqueous sizing agent for fibers, as an optional embodiment, the polyamic acid has at least one of the following structural formulas:
[0085]
[0086]
[0087] In the above-mentioned aqueous sizing agent for fibers, as an optional embodiment, the number average molecular weight of the polyamic acid ranges from 1000 to 100000 g / mol (for example, it can be 1000 g / mol, 5000 g / mol, 10000 g / mol, 30000 g / mol, 50000 g / mol, 70000 g / mol or 100000 g / mol), preferably, the number average molecular weight of the polyamic acid ranges from 10000 to 50000 g / mol.
[0088] In the above aqueous sizing agent for fibers, as an optional implementation, the amine compound includes at least one of ammonia water, diethanolamine, triethanolamine, triethylamine, and N,N′-dimethylethanolamine.
[0089] In the above-mentioned aqueous sizing agent for fibers, as an optional embodiment, the structural formula of the sulfonated polyaramid is as follows:
[0090]
[0091] Wherein, n is a natural number greater than 0;
[0092] R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 are the same or different and each independently represents hydrogen, sulfonic acid or salt-type sulfonic acid. Preferably, R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 are the same or different and each independently represents hydrogen, sulfonic acid group or sodium salt type sulfonic acid group;
[0093] Ar2 is one or more of the following structures:
[0094]
[0095] Among them, R 14 , R 15 , R 16 , R 17 , R 18 , R 19 , R 20 , R 21 , R 22 , R 23 , R 24 , R 25 , R 26 , R 27 , R 28 , R29 , R 30 , R 31 , R 32 , R 33 , R 34 , R 35 , R 36 , R 37 , R 38 , R 39 , R 40 , R 41 , R 42 , R 43 , R 44 , R 45 , R 46 , R 47 , R 48 , R 49 are the same or different and each independently represents hydrogen, sulfonic acid or salt-type sulfonic acid. Preferably, R 14 , R 15 , R 16 , R 17 , R 18 , R 19 , R 20 , R 21 , R 22 , R 23 , R 24 , R 25 , R 26 , R 27 , R 28 , R 29 , R 30 , R 31 , R 32 , R 33 , R 34 , R 35 , R 36 , R 37 , R 38 , R 39 , R 40 , R 41 , R 42 , R 43 , R 44 , R 45 , R 46 , R 47 , R 48 , R 49 are the same or different and each independently represents hydrogen, sulfonic acid group or sodium salt type sulfonate group.
[0096] In the above-mentioned aqueous sizing agent for fibers, as an optional embodiment, the sulfonated polyaramid has at least one of the following structural formulas:
[0097]
[0098]
[0099] In the above aqueous sizing agent for fibers, as an optional implementation, the lignin sulfonate includes sodium lignin sulfonate.
[0100] Specifically, the lignin sulfonate is composed of the following three basic structural units connected by carbon-oxygen bonds and carbon-carbon bonds, and is a complex macromolecule with a three-dimensional network structure having aromatic properties:
[0101]
[0102] In the above-mentioned aqueous sizing agent for fibers, as an optional embodiment, the number average molecular weight of the sulfonated polyaromatic amide is 1000 to 100000 g / mol (for example, it can be 1000 g / mol, 5000 g / mol, 10000 g / mol, 30000 g / mol, 50000 g / mol, 70000 g / mol or 100000 g / mol), preferably, the number average molecular weight of the sulfonated polyaromatic amide ranges from 10000 to 50000 g / mol.
[0103] In the above-mentioned aqueous sizing agent for fibers, as an optional embodiment, the number average molecular weight of the lignin sulfonate is 1000-250000 g / mol (for example, it can be 1000 g / mol, 5000 g / mol, 10000 g / mol, 30000 g / mol, 50000 g / mol, 100000 g / mol, 150000 g / mol, 200000 g / mol or 250000 g / mol), preferably, the number average molecular weight is 10000-50000 g / mol.
[0104] In the above-mentioned aqueous sizing agent for fibers, as an optional embodiment, the fibers (the type of fibers sizing thereof) include at least one of carbon fibers, basalt fibers, quartz fibers, glass fibers, and silicon carbide fibers, and the fiber types are not limited to fabrics, continuous fibers, and chopped fibers.
[0105] In a second aspect, the present invention provides a method for preparing the aqueous sizing agent for fibers as described in the first aspect, the preparation method comprising the following steps:
[0106] Dissolving the component 1 in the water to obtain a component 1 solution;
[0107] Dissolving the component 2 in the water to obtain a component 2 solution;
[0108] The component 1 solution and the component 2 solution are mixed to obtain the aqueous sizing agent for the fiber.
[0109] In the method for preparing the aqueous sizing agent for fibers, as an optional embodiment, in the component 1 solution, the mass ratio of the component 1 to the water is 1:(4-100), for example, 1:4, 1:50, 1:60, 1:80 or 1:100.
[0110] In the above-mentioned method for preparing the aqueous sizing agent for fibers, as an optional embodiment, the particle size range of the component 1 solution is 5 to 4500 nm (for example, it can be 5 nm, 100 nm, 500 nm, 1000 nm, 2000 nm, 3000 nm, 4000 nm or 4500 nm), preferably 50 nm to 500 nm (for example, it can be 50 nm, 100 nm, 200 nm, 300 nm, 400 nm or 500 nm).
[0111] In the method for preparing the aqueous sizing agent for fibers, as an optional embodiment, in the solution of component 2, the mass ratio of component 2 to water is 1:(0.5-500), for example, it can be 1:0.5, 1:100, 1:200, 1:300, 1:400 or 1:500.
[0112] In the above-mentioned method for preparing the aqueous sizing agent for fibers, as an optional embodiment, the particle size range of the component 2 solution is 5 to 4500 nm (for example, it can be 5 nm, 100 nm, 500 nm, 1000 nm, 2000 nm, 3000 nm, 4000 nm or 4500 nm), preferably 50 nm to 500 nm (for example, it can be 50 nm, 100 nm, 200 nm, 300 nm, 400 nm or 500 nm), preferably 50 nm to 500 nm (for example, it can be 50 nm, 100 nm, 200 nm, 300 nm, 400 nm or 500 nm).
[0113] In a third aspect, the present invention provides a use of the aqueous sizing agent for fibers as described in the first aspect in fibers.
[0114] Specifically, a modified fiber, the preparation process of which includes the following steps: immersing unsized or desized fiber bundles in the aqueous sizing agent for the fibers, and drying after sizing to obtain the modified fiber.
[0115] A fiber-reinforced polyamide resin composite material comprises the modified fiber and polyamide resin.
[0116] The application of the above-mentioned aqueous sizing agent for fibers in fibers, as an optional implementation, the aqueous sizing agent for fibers is applied to a composite material of fiber-reinforced polyamide resin, wherein the polyamide resin includes at least one of polyamide 6 (PA6), polyamide 66 (PA66), polydecane terephthalamide (PA10T), and polyhexamethylene terephthalamide (PA6T).
[0117] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.
[0118] Example 1
[0119] The present embodiment provides an aqueous sizing agent for carbon fiber, the aqueous sizing agent for carbon fiber comprising component 1, component 2 and deionized water, wherein the component 1 is polyamic acid ammonium salt, and the component 2 is sulfonated polyaramid; based on the total weight of the aqueous sizing agent for carbon fiber being 100 parts, the aqueous sizing agent for carbon fiber comprises the following components in parts by weight:
[0120] Component 1: 0.1 part
[0121] Component 2: 14 parts
[0122] Deionized water: 85.9 parts;
[0123] The polyamic acid ammonium salt has a number average molecular weight of 5000 g / mol and is formed by the reaction of polyamic acid and diethanolamine. The specific preparation method includes the following steps: setting the molar ratio of dianhydride to diamine to 1.01:1, adding 1,6-hexanediamine to N,N-dimethylformamide under ice-water bath conditions and stirring to form a solution, adding pyromellitic acid dianhydride to the solution in batches, and continuing to stir until the viscosity no longer increases after the addition of pyromellitic acid dianhydride. Subsequently, adding diethanolamine and stirring at high speed, precipitating in acetone, and drying to obtain the polyamic acid ammonium salt.
[0124] Wherein, the structural formula of the polyamic acid is as follows:
[0125]
[0126] The structural formula of the diethanolamine is shown below:
[0127]
[0128] The number average molecular weight of the sulfonated polyaromatic amide is 50000 g / mol, and the structural formula is as follows:
[0129]
[0130] The preparation method of the sulfonated polyaromatic amide comprises the following steps: adding a diacid containing a diazinone structure, p-phenylenediamine, anhydrous calcium chloride, triphenyl phosphite, and pyridine to N-methylpyrrolidone under a nitrogen atmosphere, stirring at 110° C. until the viscosity no longer increases, and pouring into an ethanol / water solution to obtain polyaromatic amide. The dried polyaromatic amide powder is added to concentrated sulfuric acid, reacted at 60° C. for 3 hours, and precipitated in an ice-water bath to obtain sulfonated polyaromatic amide. The preparation method of the aqueous sizing agent for carbon fiber provided in this embodiment comprises the following steps:
[0131] Step 1: dissolving 0.1 parts by weight of component 1 in 10 parts by weight of deionized water to obtain a component 1 solution, wherein the average particle size of the obtained solution is 5 nm (measured by DLS light scattering);
[0132] Step 2: dissolving 14 parts by weight of component 2 in 75.9 parts by weight of deionized water to obtain a component 2 solution, wherein the average particle size of the obtained solution is 50 nm (measured by DLS light scattering);
[0133] Step 3: Mix the solution of component 1 and the solution of component 2 to form a uniform solution to obtain an aqueous sizing agent for carbon fiber.
[0134] Application to carbon fiber: The desized carbon fiber fabric is immersed in the aqueous sizing agent obtained in step 3 at 25° C. for 20 minutes. After sizing, the sized carbon fiber fabric is dried at 180° C. for 30 minutes to completely evaporate the water to obtain a sized carbon fiber fabric.
[0135] Composite materials applied to carbon fiber reinforced polyamide resin: the sizing carbon fiber fabric and polyamide 6 (PA6) resin are hot-pressed in a mass ratio of 5:5 to obtain a composite material.
[0136] Depend on Figure 1 Scanning electron microscope photographs of desized carbon fiber fabric and sized carbon fiber fabric show that the surface of desized carbon fiber fabric shows relatively more grooves, while the sized carbon fiber fabric shows that the fiber grooves are filled, which indicates that the sizing agent has a good adsorption effect on the fiber.
[0137] Depend on Figure 3 The scanning electron microscopy of the cross section of the sized carbon fiber fabric / polyamide 6 resin composite after the bending test shows that the interface bonding force between the sized carbon fiber fabric and the resin matrix is stronger than that of the desized carbon fiber / resin matrix composite ( Figure 2 ), more resin adheres to the surface of the sized carbon fiber.
[0138] Depend on Figure 4 From the digital photos of sized carbon fiber tows and desized carbon fiber tows, it can be seen that the desized carbon fiber has poor bundling properties, while the sized carbon fiber has good bundling properties.
[0139] Example 2
[0140] The present embodiment provides an aqueous sizing agent for carbon fiber, the aqueous sizing agent for carbon fiber comprising component 1, component 2 and deionized water, wherein the component 1 is polyamic acid ammonium salt, and the component 2 is sulfonated polyaramid; based on the total weight of the aqueous sizing agent for carbon fiber being 100 parts, the aqueous sizing agent for carbon fiber comprises the following components in parts by weight:
[0141] Component 1: 10 parts
[0142] Component 2: 0.1 part
[0143] Deionized water: 89.9 parts;
[0144] The number average molecular weight of the polyamic acid ammonium salt is 75000g / mol, and it is formed by the reaction of polyamic acid and triethylamine. The specific preparation method includes the following steps: setting the molar ratio of dianhydride to diamine to 1.01:1, adding 1,4-bis(3-aminopropyl)piperazine to N,N-dimethylformamide under ice-water bath conditions, stirring to form a solution, adding 3,3',4,4'benzophenone tetracarboxylic acid dianhydride to the solution in batches, and continuing to stir until the viscosity no longer increases after the addition of 3,3',4,4'benzophenone tetracarboxylic acid dianhydride. Subsequently, adding triethylamine with high-speed stirring, settling in acetone to precipitate, and drying to obtain the polyamic acid ammonium salt.
[0145] Wherein, the structural formula of the polyamic acid is as follows:
[0146]
[0147] The structural formula of the triethylamine is shown below:
[0148]
[0149] The number average molecular weight of the sulfonated polyaromatic amide is 1000 g / mol, and the structural formula is as follows:
[0150]
[0151] The preparation method of the sulfonated polyaromatic amide comprises the following steps: adding a diacid containing a diazinone structure, 4,4'-diaminodiphenyl ether, anhydrous calcium chloride, triphenyl phosphite, and pyridine to N-methylpyrrolidone under a nitrogen atmosphere, stirring at 110°C until the viscosity no longer increases, and pouring into an ethanol / water solution to obtain polyaromatic amide. The dried polyaromatic amide powder is added to concentrated sulfuric acid, reacted at 60°C for 4 hours, solids are precipitated in an ice-water bath, and the dried solids are reacted with sodium hydroxide to obtain the sulfonated polyaromatic amide. The preparation method of the aqueous sizing agent for carbon fiber provided in this embodiment comprises the following steps:
[0152] Step 1: dissolving 10 parts by weight of component 1 in 50 parts by weight of deionized water to obtain a component 1 solution, wherein the average particle size of the obtained solution is 500 nm;
[0153] Step 2: dissolving 0.1 parts by weight of component 2 in 39.9 parts by weight of deionized water to obtain a component 2 solution, wherein the average particle size of the obtained solution is 4500 nm;
[0154] Step 3: Mix the solution of component 1 and the solution of component 2 to form a uniform solution to obtain an aqueous sizing agent for carbon fiber. Application to carbon fiber: Immerse the desized carbon fiber fabric in the aqueous sizing agent obtained in step 3 for 20 minutes. After sizing, dry the sized carbon fiber fabric at 180° C. for 30 minutes to completely evaporate the water to obtain a sized carbon fiber fabric.
[0155] Composite materials applied to carbon fiber reinforced polyamide resin: the sizing carbon fiber fabric is cut into short pieces and then hot-pressed with polyamide 66 (PA66) resin at a mass ratio of 1:9 to obtain a composite material.
[0156] Example 3
[0157] The present embodiment provides an aqueous sizing agent for carbon fiber, the aqueous sizing agent for carbon fiber comprising component 1, component 2 and deionized water, wherein the component 1 is polyamic acid ammonium salt, and the component 2 is sulfonated polyaramid; based on the total weight of the aqueous sizing agent for carbon fiber being 100 parts, the aqueous sizing agent for carbon fiber comprises the following components in parts by weight:
[0158] Component 1: 15 parts
[0159] Component 2: 15 parts
[0160] Deionized water: 70 parts;
[0161] The polyamic acid ammonium salt has a number average molecular weight of 25000 g / mol and is formed by the reaction of polyamic acid and ammonia water. The specific preparation method includes the following steps: setting the molar ratio of dianhydride to diamine to 1.01:1, adding 3,3′-dimethyl-4,4′-diaminodicyclohexyl methane to N,N-dimethylformamide under ice-water bath conditions and stirring to form a solution, adding cyclobutane tetracarboxylic dianhydride to the solution in batches, and continuing to stir until the viscosity no longer increases after the addition of cyclobutane tetracarboxylic dianhydride. Subsequently, adding ammonia water and stirring at high speed, precipitating in acetone, and drying to obtain the polyamic acid ammonium salt.
[0162] Wherein, the structural formula of the polyamic acid is as follows:
[0163]
[0164] The number average molecular weight of the sulfonated polyaromatic amide is 45000 g / mol, and the structural formula is as follows:
[0165]
[0166] The preparation method of the sulfonated polyaromatic amide comprises the following steps: adding a diacid containing a phthalazinone structure, 4,4'-diaminodiphenyl sulfone, anhydrous calcium chloride, triphenyl phosphite, and pyridine to N-methylpyrrolidone under a nitrogen atmosphere, stirring at 110° C. until the viscosity no longer increases, and pouring into an ethanol / water solution to obtain polyaromatic amide. Adding the dried polyaromatic amide powder to concentrated sulfuric acid, reacting at 60° C. for 4 hours, precipitating in an ice-water bath to obtain a solid, and reacting the dried solid with sodium hydroxide to obtain the sulfonated polyaromatic amide.
[0167] The preparation method of the aqueous sizing agent for carbon fiber provided in this embodiment comprises the following steps:
[0168] Step 1: dissolving 15 parts by weight of component 1 in 60 parts by weight of deionized water to obtain a component 1 solution, wherein the average particle size of the obtained solution is 400 nm;
[0169] Step 2: dissolving 15 parts by weight of the component 2 resin in 10 parts by weight of deionized water to obtain a component 2 solution, wherein the average particle size of the obtained solution is 300 nm;
[0170] Step 3: Mix the solution of component 1 and the solution of component 2 to form a uniform solution to obtain an aqueous sizing agent for carbon fiber.
[0171] Application to carbon fiber: The desized carbon fiber is immersed in the aqueous sizing agent obtained in step 3 for 20 minutes. After that, the sized carbon fiber is dried at 180° C. for 30 minutes to completely evaporate the water, thereby obtaining the sized carbon fiber.
[0172] Composite materials applied to carbon fiber reinforced polyamide resin: after the sizing carbon fiber is cut short, the short carbon fiber and polydecane terephthalamide (PA10T) resin are hot-pressed at a mass ratio of 1:9 to obtain a composite material.
[0173] Example 4
[0174] The present embodiment provides an aqueous sizing agent for carbon fiber, the aqueous sizing agent for carbon fiber comprising component 1, component 2 and deionized water, wherein the component 1 is polyamic acid ammonium salt, and the component 2 is sulfonated polyaramid; based on the total weight of the aqueous sizing agent for carbon fiber being 100 parts, the aqueous sizing agent for carbon fiber comprises the following components in parts by weight:
[0175] Component 1: 7.5 parts
[0176] Component 2: 5 parts
[0177] Deionized water: 87.5 parts;
[0178] The polyamic acid ammonium salt has a number average molecular weight of 50,000 g / mol and is formed by the reaction of polyamic acid and triethanolamine. The specific preparation method includes the following steps: setting the molar ratio of dianhydride to diamine to 1.01:1, adding 1,6-hexanediamine to N,N-dimethylformamide under ice-water bath conditions and stirring to form a solution, adding pyromellitic acid dianhydride to the solution in batches, and continuing to stir until the viscosity no longer increases after the addition of pyromellitic acid dianhydride. Subsequently, adding triethanolamine and stirring at high speed, precipitating in acetone, and drying to obtain the polyamic acid ammonium salt.
[0179] Wherein, the structural formula of the polyamic acid is as follows:
[0180]
[0181] The structural formula of the triethanolamine is shown below:
[0182]
[0183] The number average molecular weight of the sulfonated polyaromatic amide is 100000 g / mol, and the structural formula is as follows:
[0184]
[0185] The preparation method of the sulfonated polyaromatic amide comprises the following steps: adding a diacid containing a phthalazinone structure, 4,4'-diaminobenzophenone, anhydrous calcium chloride, triphenyl phosphite, and pyridine to N-methylpyrrolidone under a nitrogen atmosphere, stirring at 110° C. until the viscosity no longer increases, and pouring into an ethanol / water solution to obtain polyaromatic amide. Adding the dried polyaromatic amide powder to concentrated sulfuric acid, reacting at 60° C. for 4 hours, precipitating in an ice-water bath to obtain a solid, and reacting the dried solid with sodium hydroxide to obtain the sulfonated polyaromatic amide.
[0186] The preparation method of the aqueous sizing agent for carbon fiber provided in this embodiment comprises the following steps:
[0187] Step 1: dissolving 7.5 parts by weight of component 1 in 30 parts by weight of deionized water to obtain a component 1 solution, wherein the average particle size of the obtained solution is 4500 nm;
[0188] Step 2: dissolving 5 parts by weight of the component 2 resin in 57.5 parts by weight of deionized water to obtain a component 2 solution, wherein the average particle size of the obtained solution is 180 nm;
[0189] Step 3: Mix the solution of component 1 and the solution of component 2 to form a uniform solution to obtain an aqueous sizing agent for carbon fiber.
[0190] Application to carbon fiber: The desized continuous carbon fiber is immersed in the aqueous sizing agent obtained in step 3 for 20 minutes. After sizing, the sized continuous carbon fiber is dried at 180° C. for 30 minutes to completely evaporate the water, thereby obtaining sized carbon fiber.
[0191] Composite materials applied to carbon fiber reinforced polyamide resin: the sized continuous carbon fiber and polyamide 6 (PA6) resin are hot-pressed in a volume ratio of 6:4 to obtain a composite material.
[0192] Example 5
[0193] The present embodiment provides an aqueous sizing agent for carbon fiber, the aqueous sizing agent for carbon fiber comprising component 1, component 2 and deionized water, wherein the component 1 is polyamic acid ammonium salt, and the component 2 is sodium lignin sulfonate; based on the total weight of the aqueous sizing agent for carbon fiber being 100 parts, the aqueous sizing agent for carbon fiber comprises the following components in parts by weight:
[0194] Component 1: 0.1 part
[0195] Component 2: 14 parts
[0196] Deionized water: 85.9 parts;
[0197] The polyamic acid ammonium salt has a number average molecular weight of 5000 g / mol and is formed by the reaction of polyamic acid and diethanolamine. The specific preparation method includes the following steps: setting the molar ratio of dianhydride to diamine to 1.01:1, adding 1,6-hexanediamine to N,N-dimethylformamide under ice-water bath conditions and stirring to form a solution, adding pyromellitic acid dianhydride to the solution in batches, and continuing to stir until the viscosity no longer increases after the addition of pyromellitic acid dianhydride. Subsequently, adding diethanolamine and stirring at high speed, precipitating in acetone, and drying to obtain the polyamic acid ammonium salt.
[0198] Wherein, the structural formula of the polyamic acid is as follows:
[0199]
[0200] The structural formula of the diethanolamine is shown below:
[0201]
[0202] The sodium lignin sulfonate has a number average molecular weight of 20,000 g / mol and is purchased from Aladdin Reagent Network.
[0203] The preparation method of the aqueous sizing agent for carbon fiber provided in this embodiment comprises the following steps:
[0204] Step 1: dissolving 0.1 parts by weight of component 1 in 10 parts by weight of deionized water to obtain a component 1 solution, wherein the average particle size of the obtained solution is 5 nm;
[0205] Step 2: dissolving 14 parts by weight of component 2 in 75.9 parts by weight of deionized water to obtain a component 2 solution, wherein the average particle size of the obtained solution is 250 nm;
[0206] Step 3: Mix the solution of component 1 and the solution of component 2 to form a uniform solution to obtain an aqueous sizing agent for carbon fiber.
[0207] Application to carbon fiber: The desized carbon fiber fabric is immersed in the aqueous sizing agent obtained in step 3 for 20 minutes. After sizing, the sized carbon fiber fabric is dried at 180° C. for 30 minutes to completely evaporate the water, thereby obtaining a sized carbon fiber fabric.
[0208] Composite materials applied to carbon fiber reinforced polyamide resin: the sizing carbon fiber fabric and polyamide 6 (PA6) resin are hot-pressed in a mass ratio of 5:5 to obtain a composite material.
[0209] Comparative Example 1
[0210] In this comparative example 1, carbon fiber fabric that has not been subjected to sizing treatment and polyamide 6 (PA6) resin are hot-pressed in a mass ratio of 5:5 to obtain a composite material.
[0211] Depend on Figure 2 Scanning electron microscopy of the cross-section of the desized carbon fiber fabric / polyamide 6 resin composite material after the bending test showed that the interface bonding strength between the desized carbon fiber fabric and the resin matrix was poor, and little resin adhered to the fiber surface.
[0212] Comparative Example 2
[0213] In this comparative example 2, short-cut carbon fiber fabrics that have not been sizing treated are hot-pressed with polyamide 66 (PA66) resin in a mass ratio of 1:9 to obtain a composite material.
[0214] Comparative Example 3
[0215] In this comparative example 3, short-cut carbon fibers that have not been sizing treated are hot-pressed with polydecane terephthalamide (PA10T) resin in a mass ratio of 1:9 to obtain a composite material.
[0216] Comparative Example 4
[0217] In this comparative example 4, continuous carbon fibers that have not been sizing treated are hot-pressed with polyamide 6 (PA6) resin in a volume ratio of 6:4 to obtain a composite material.
[0218] Comparative Example 5
[0219] The carbon fiber provided in this comparative example is a commercial carbon fiber fabric purchased from Toray Industries, Ltd. of Japan, and the fiber surface is coated with a commercial epoxy sizing agent.
[0220] Composite materials applied to carbon fiber reinforced polyamide resin: Commercial carbon fiber fabric and polyamide 6 (PA6) resin are hot-pressed in a mass ratio of 5:5 to obtain a composite material.
[0221] Comparative Example 6
[0222] The aqueous sizing agent for carbon fiber provided in this comparative example is substantially the same as that in Example 1, except that the aqueous sizing agent for carbon fiber does not include component 2. Specifically, the aqueous sizing agent for carbon fiber includes component 1 and deionized water, wherein component 1 is polyamic acid ammonium salt; based on 100 parts by weight of the total parts by weight of the aqueous sizing agent for carbon fiber, the aqueous sizing agent for carbon fiber includes the following components in parts by weight:
[0223] Component 1: 14.1 parts
[0224] 85.9 parts of deionized water.
[0225] The preparation method of the aqueous sizing agent for carbon fiber provided in this embodiment comprises the following steps:
[0226] 14.1 parts by weight of component 1 were dissolved in 85.9 parts by weight of deionized water, and the mixture was mixed to form a uniform solution to obtain an aqueous sizing agent for carbon fiber.
[0227] Application to carbon fiber: The desized carbon fiber fabric is immersed in the aqueous sizing agent provided in this comparative example at 25°C for 20 minutes. After sizing, the sized carbon fiber fabric is dried at 180°C for 30 minutes to completely evaporate the water to obtain a sized carbon fiber fabric.
[0228] Composite materials applied to carbon fiber reinforced polyamide resin: the sizing carbon fiber fabric and polyamide 6 (PA6) resin are hot-pressed in a mass ratio of 5:5 to obtain a composite material.
[0229] Performance Testing
[0230] Test 1
[0231] The mechanical properties of the fiber reinforced polyamide resin composite materials obtained in the examples and comparative examples were tested. The test results are shown in Tables 1 and 2.
[0232] The composite materials obtained from Example 1, Examples 4-5 and Comparative Examples 1 and Comparative Examples 4-6 were tested:
[0233] (1) Interlaminar shear test: The test method refers to ISO14130 standard. The three-point short arm beam bending method is used to test the interlaminar shear performance of the composite material. The specimen size is 20 mm*10 mm*2 mm, the test span is 5 times the specimen thickness, and the load loading rate is 1 mm / min.
[0234] (2) Flexural strength test: The test method refers to ASTM D790, and the flexural strength of the composite material is tested using a three-point bending mode. The sample size is 80 mm*12.5 mm*2 mm, the indenter advance rate is 2 mm / min, and the sample span to thickness ratio is 32:1.
[0235] The composite materials obtained from Examples 2-3 and Comparative Examples 2-3 were tested:
[0236] (1) Tensile strength test: The test method refers to the test standard GB / T-1447-2005, the specimen length is 175 mm, the width is 25 mm, and the test fixture loading rate is 2 mm / min.
[0237] (2) Bending strength test: The test method is based on GB / T9341-2008. The three-point bending mode is used to test the bending strength of the composite material. The sample size is 80 mm*10 mm*4 mm, the indenter forward speed is 2 mm / min, and the sample span is 64 mm.
[0238] Table 1
[0239] Interlaminar shear strength (MPa) Bending strength(MPa) Example 1 105 1270 Example 4 103 2105 Example 5 80 1004 Comparative Example 1 56 603 Comparative Example 4 68 1250 Comparative Example 5 53 507 Comparative Example 6 70 909
[0240] Table 2
[0241] Bending strength(MPa) Tensile strength(MPa) Example 2 151 101 Example 3 138 97 Comparative Example 2 107 80 Comparative Example 3 103 78
[0242] Test 2
[0243] The following tests were performed on the unsizing carbon fiber fabric (desized carbon fiber) and the sizing carbon fiber obtained in the above examples and comparative examples 5-6:
[0244] Fiber fuzzing test: The fiber fuzzing test method is based on GB / T4195 6-2022. The fiber passes through 4 guide rods at a speed of 15m / min, and then passes through the polyurethane foam. A 100g loading block is placed above the foam. The running length is set to 50m, and the mass of the fuzz collected on the polyurethane foam is weighed.
[0245] The test results are shown in Table 3.
[0246] Table 3
[0247] Fluffing amount (mg / 50m) Example 1 1.0 Example 2 1.5 Example 3 1.7 Example 4 1.2 Example 5 1.2 Comparative Example 5 2.0 Comparative Example 6 3.2 Comparative example of desizing carbon fiber 14.1
[0248] From Table 1-3, we can see at least the following points:
[0249] (1) By comparing Examples 1-5 with Comparative Examples 1-4, it can be seen that after the fibers are treated with the aqueous sizing agent provided by the present invention, the interlaminar shear strength, bending strength and tensile strength of the fiber-reinforced composite material can be effectively improved, indicating that after the fibers are treated with the aqueous sizing agent provided by the present invention, the interfacial bonding strength between the fibers and the polyamide matrix can be made higher.
[0250] (2) By comparing Example 1 with Comparative Example 5, it can be seen that compared with the commercial epoxy sizing agent, the aqueous sizing agent provided by the present invention can increase the interfacial bonding strength between the fiber and the polyamide matrix.
[0251] (3) By comparing Example 1 with Comparative Example 6, it can be seen that when the aqueous sizing agent only includes component 1, the interfacial bonding strength between the fiber and the polyamide matrix decreases. The applicant speculates that the reason may be that Comparative Example 6 is a single-component sizing agent, which only relies on the chemical force between the sizing agent and the matrix, while the two-component sizing agent mentioned in the present invention not only has chemical force, but also causes irregular infiltration of the matrix on the fiber surface due to the difference in rheological behavior of the two components, and the contact area between the matrix and the fiber will increase. When the material is subjected to external force, the pull-off work between the matrix and the fiber is large, resulting in enhanced interfacial bonding.
[0252] (4) By comparing Examples 1-5 with the desized carbon fibers, it can be seen that the amount of fuzzing can be reduced after sizing the carbon fibers with the aqueous sizing agent provided by the present invention. The above results indicate that the sized fibers are not prone to fuzzing and have good processing performance.
[0253] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A water-based sizing agent for fibers, characterized in that: The aqueous sizing agent for fibers comprises component 1, component 2 and water, wherein component 1 is polyamic acid salt, and component 2 is at least one of sulfonated polyaramid and lignin sulfonate; based on 100 parts by weight of the total parts by weight of the aqueous sizing agent for fibers, the aqueous sizing agent for fibers comprises the following components in parts by weight: Component 1: 0.1-15 parts; Component 2: 0.1-15 parts; Water: 70-99.8 parts.
2. The aqueous sizing agent for fibers according to claim 1, characterized in that The water includes deionized water; And / or, the main chain of the molecule of component 1 contains a fatty chain structure, and the main chain of the molecule of component 2 contains a heterocyclic structure; And / or, the component 1 is a polyamic acid ammonium salt formed by polyamic acid and an amine compound.
3. The aqueous sizing agent for fibers according to claim 2, characterized in that The polyamic acid is prepared by polymerization of a dianhydride monomer and a diamine monomer, wherein the dianhydride monomer includes at least one of 1,2,3,4-butanetetracarboxylic dianhydride, cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, 1,2,3,4-cyclohexanetetracarboxylic dianhydride, pyromellitic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 4,4'-biphenyl ether dianhydride, and 3,4,3',4'-biphenyltetracarboxylic dianhydride, and the diamine monomer is selected from the group consisting of: The amine monomer includes at least one of hexamethylenediamine, 1,5-diamino-2-methylpentane, nonanediamine, 3-methylheptanediamine, 4,4-dimethylheptanediamine, decanediamine, polyethylene oxide diamine, 2,2′-(ethylenedioxy)diethylamine, bis(3-aminopropyl)amine, 1,4-bis(3-aminopropyl)piperazine, diaminobutene dinitrile, polyether diamine, 1,4-cyclohexanediamine, 5-amino-1,3,3-trimethylcyclohexanemethylamine, 4,4′-diaminodicyclohexylmethane, and 3,3′-dimethyl-4,4′-diaminodicyclohexylmethane; And / or, the structural formula of the polyamic acid is as follows: Wherein, n is a natural number greater than 0; Ar1 is at least one of the following structures: -L- is at least one of the following structures:
4. The aqueous sizing agent for fibers according to claim 2, characterized in that The polyamic acid has at least one of the following structural formulas: And / or, the number average molecular weight of the polyamic acid is in the range of 1000 to 100000 g / mol; And / or, the amine compound includes at least one of ammonia water, diethanolamine, triethanolamine, triethylamine, and N,N′-dimethylethanolamine.
5. The aqueous sizing agent for fibers according to claim 1, characterized in that: The structural formula of the sulfonated polyaromatic amide is shown below: Wherein, n is a natural number greater than 0; R2, R3, R4, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 are the same or different and each independently represents hydrogen, sulfonic acid group or salt-type sulfonic acid group; Ar2 is one or more of the following structures: Among them, R 14 , R 15 , R 16 , R 17 , R 18 , R 19 , R 20 , R 21 , R 22 , R 23 , R 24 , R 25 , R 26 , R 27 , R 28 , R 29 , R 30 , R 31 , R 32 , R 33 , R 34 , R 35 , R 36 , R 37 , R 38 , R 39 , R 40 , R 41 , R 42 , R 43 , R 44 , R 45 , R 46 , R 47 , R 48 , R 49 are the same or different and each independently represents hydrogen, sulfonic acid group or salt-type sulfonic acid group; And / or, the sulfonated polyaromatic amide has at least one of the following structural formulas: and / or, the lignin sulfonate comprises sodium lignin sulfonate; and / or, the number average molecular weight of the sulfonated polyaromatic amide is 1000 to 100000 g / mol; and / or, the number average molecular weight of the lignin sulfonate is 1000-250000 g / mol; And / or, the fiber includes at least one of carbon fiber, basalt fiber, quartz fiber, glass fiber, and silicon carbide fiber.
6. A method for preparing an aqueous sizing agent for fibers as claimed in any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: Dissolving the component 1 in the water to obtain a component 1 solution; Dissolving the component 2 in the water to obtain a component 2 solution; The component 1 solution and the component 2 solution are mixed to obtain the aqueous sizing agent for the fiber.
7. The method for preparing an aqueous sizing agent for fibers according to claim 6, characterized in that: In the component 1 solution, the mass ratio of the component 1 to the water is 1:(4-100); and / or, the particle size of the component 1 solution ranges from 5 to 4500 nm; and / or, in the component 2 solution, the mass ratio of the component 2 to the water is 1:(0.5-500); And / or, the particle size range of the component 2 solution is 5 to 4500 nm.
8. Use of the aqueous sizing agent for fibers as claimed in any one of claims 1 to 5 in fibers.
9. A modified fiber, characterized in that: The preparation process of the modified fiber comprises the following steps: immersing unsized or desized fiber tows in the aqueous fiber sizing agent according to any one of claims 1 to 5, and drying after sizing to obtain the modified fiber.
10. A composite material of fiber-reinforced polyamide resin, characterized in that: The method comprises the modified fiber as claimed in claim 9 and a polyamide resin.
Citation Information
Cited By
Sizing agent for quartz fiber as well as preparation method and application of sizing agent
CN121407396A
High-temperature-resistant water-based sizing agent as well as preparation method and application thereof
CN122103571A
Water-soluble polyamide sizing agent as well as preparation method and application thereof
CN122213404A